Identification of Chlorobenzene in the Viking Gas Chromatograph‐Mass Spectrometer Data Sets: Reanalysis of Viking Mission Data Consistent With Aromatic Organic Compounds on Mars. Issue 7 (12th July 2018) - Guzman, Melissa; McKay, Christopher P.; Quinn, Richard C.; Szopa, Cyril; Davila, Alfonso F.; Navarro‐González, Rafael; Freissinet, Caroline
Abstract: Motivated by the recent detection of chlorobenzene by the Sample Analysis at Mars instrument suite on the Curiosity rover, and the identification of its carbon source as indigenous to the martian sample, we reexamined the original, microfilm preserved, Viking gas chromatograph‐mass spectrometer data sets. We found evidence for the presence of chlorobenzene in Viking Lander 2 (VL‐2) data at levels corresponding to 0.08–1.0 ppb (relative to sample mass), in runs when the sample was heated to 350°C and 500°C. Additionally, we found a correlation between the temperature dependence of the chlorobenzene signal and the dichloromethane signal originally identified by the Viking gas chromatograph‐mass spectrometer team. We considered possible sources of carbon that may have produced the chlorobenzene signal, by reaction with perchlorate during pyrolysis, including organic carbon indigenous to the martian parent sample and instrument contamination. We conclude that the chlorobenzene signal measured by VL‐2 originated from martian chlorine sources. We show how the carbon source could originate from the martian parent sample, though a carbon source contributed from instrument background cannot yet be ruled out. Plain Language Summary: The first successful landers on Mars were the twin Viking spacecraft in 1976. Their primary goal was to determine if life could survive on Mars. The Viking landers looked for organic matter in the martian soil. Organics are critical for astrobiology since carbon forms the key ingrediant for all known living organisms on Earth. Shockingly, a main instrument on the landers, the gas chromatograph‐mass spectrometer, detected no organic matter. This was a surprise to scientists, who knew organic material was deposited by comets and meteorites to the martian surface. The apparent absence of organic molecules in the martian surface material became a scientific mystery for decades. In 2008, the Phoenix spacecraft explored the north pole of Mars. Phoenix discovered a salt in the martian soil which is rare on Earth. After further conclusions of the presence of this salt on Mars and complemental experiments on Earth, scientists proposed this salt might have chlorinated any organics inside the Viking instruments. We searched the Viking data for a possible reaction product between the salt and organics in the Viking oven, chlorobenzene, a chlorinated organic molecule. We found evidence of chlorobenzene. We conclude the chlorine component of the chlorobenzene is martian, and the carbon molecule of the chlorobenzene is consistent with a martian origin, though we cannot fully rule out instrument contamination. Key Points: Chlorobenzene is identified in Viking Lander 2 GCMS data The chlorine‐bearing molecule of the chlorobenzene signal is martian Evidence consistent with organic carbon in martian surface sediments is detected in situ by Viking Lander 2